Primary Skeletal Muscle Diffuse Large B Cell Lymphoma in Lumbar Region – A Rare Occurrence - Muralidhar, Aparna; Mahadev, Kanna Sandhyarani; Minal, Jessica; Venkatesan, Vidhya; Mysorekar, Vijaya V (International Journal of Human and Health Sciences (IJHHS), 2024)
Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma worldwide. Patients most often present with a rapidly growing tumour mass in single or multiple, nodal, or extranodal sites. Extranodal involvement is seen in up to 40% cases. Initial presentation as soft tissue lesion is rare. We report a case of extranodal DLBCL in an elderly male, presenting as a soft tissue mass in the left lumbar region, clinically suggestive of lipoma. The patient had no palpable lymphadenopathy. Complete blood counts were within normal limits. Initial ultrasonography was suggestive of abscess, possibly of tubercular origin. On fine needle aspiration cytology, features were of a malignant neoplasm; a lymphomatous process. Subsequent histopathological evaluation followed by IHC confirmed the diagnosis of DLBCL. Primary extranodal DLBCL involving the soft tissue is rare. Owing to its non- specific and unusual clinical presentation, accurate diagnosis may be delayed. Besides, imaging modalities are also diagnostically challenging due to a wide range of differentials, thereby emphasising the need for tissue diagnosis. Histopathological examination and immunohistochemistry are paramount in accurate diagnosis and tailoring treatment options. International Journal of Human and Health Sciences Vol. 08 No. 01 Jan’24 Page: 95-98